2014
DOI: 10.1007/s11442-015-1154-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of meteorological disasters based on information diffusion theory in Xinjiang, Northwest China

Abstract: Data of flood, drought, hailstorms, and low temperature events in Xinjiang from 1949 to 2012 were analyzed with the diffusion method to assess the risk of the most common types of disasters in Xinjiang. It was proved that the frequency and intensity of meteorological disasters of the study area showed an increasing trend associated with global warming. Among the four types of disasters, surpass probability of drought was the largest, followed by hailstorm, low temperature and flood in turn. Moreover, the wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This study adopts information diffusion theory to estimate the forest fire risk in provinces in China. In recent decades, information diffusion theory risk has been widely used for the risk assessment of natural disasters [58][59][60]. It applies fuzzy information to deal with samples combined with associated diffusion functions [61,62].…”
Section: Risk Assessment Based On Information Diffusion Theorymentioning
confidence: 99%
“…This study adopts information diffusion theory to estimate the forest fire risk in provinces in China. In recent decades, information diffusion theory risk has been widely used for the risk assessment of natural disasters [58][59][60]. It applies fuzzy information to deal with samples combined with associated diffusion functions [61,62].…”
Section: Risk Assessment Based On Information Diffusion Theorymentioning
confidence: 99%
“…In the Greater Metropolitan Severe Thunderstorm Warning Area of New South Wales, a significant decreasing trend in the frequency and associated magnitude (size) of hail events was identified during 1989-2013 (Rasuly et al, 2015). In China, Xie et al (2010) reported that the long-term trend of hailstorm size in four regions of China was statistically insignificant for the period of 1980-2005, but Wu et al (2015 found an increasing trend in the frequency and intensity of hailstorms in Xinjiang, Northwest China, during the period from 1949 to 2012. In the central-eastern Italian Alps, Eccel et al (2012) found that the size of hailstorms had increased, though the frequency or cumulative hit surface showed no significant change over a number of years.…”
Section: Discussionmentioning
confidence: 99%
“…In the Greater Metropolitan Severe Thunderstorm Warning Area of New South Wales, a significant decreasing trend in the frequency and associated magnitude (size) of hail events was identified during 1989-2013 (Rasuly et al, 2015). In China, Xie et al (2010) reported that the long-term trend of hailstorm size in four regions of China was statistically insignificant for the period of 1980-2005, but Wu et al (2015 found an increasing trend in the frequency and intensity of hailstorms in Xinjiang, Northwest China, during the period from 1949 to 2012. In the central-eastern Italian Alps, Eccel et al (2012) found that the size of hailstorms had increased, though the frequency or cumulative hit surface showed no significant change over a number of years.…”
Section: Discussionmentioning
confidence: 99%